Estado actual del registro de escamados extinguidos de América del Sur y sus implicancias paleoambientales - Albino, Adriana María (1994)
The record of the South American fossil Squamata extends from the Late Cretaceous to the Holocene. The recorded families are Iguanidae s.l., Teiidae, Gekkonidae, ?Scincidae, Amphisbaenidae, Boidae, Aniliidae, Colubridae and Viperidae Dinilysiidae from the Late Cretaceous of Patagonia and Palaeopheidae from the Late Eocene of Ecuador are the only known extinct recorded families. The families distribution during the Cretaceous and most of the Tertiary apparently was more extensive than at present, due to more generalized subtropical climatic conditions. The geological events during the Cenozoic would have caused climatic and environmental changes that would have favoured the appeareance of new adaptative types and the restriction in the distribution of many forms.